Multi-representation-based interactive physics electronic module as teaching materials in online learning - Rahmawati, Irma; Nisrina, Nada; Abdani, M Rezalul (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
This study aims to describe the validity and practicality of the Interactive Physics Electronic Module (IPEMo) based on multiple representations. This study uses the ADDIE research and development method to produce a product in the form of a multi-representation-based IPEMo on the magnetic field. Product validity is viewed from the material aspect which was validated by 2 material experts and the media aspect validated by 2 media experts. The product practicality test was carried out on respondents consisting of 16 students of Tadris Fisika UIN Antasari Banjarmasin using a practicality questionnaire. Descriptive analysis was carried out on the validity and practicality of the product. The results showed that in the material aspect, the product was included in the very valid category with details on the subject matter 94%, auxiliary information 90%, affective considerations 80%, and pedagogy 90%. In the media aspect, the product is also declared to be very valid with the percentage of details on each aspect of the interface 97%, navigation 100%, and robustness 100%. The level of practicality of the product according to the respondents is included in the very practical category with details of subject matter 95%, auxiliary information 94%, affective considerations 94%, pedagogy 94%, interface 91%, navigation 98%, and robustness 93%. The results of this study have implications for the provision of valid and practical magnetic field teaching materials for use in online learning.